The Effects of Acupuncture at Sobu (HT8) and Haenggan (LR2) on Scopolamine-induced Cognitive Impairment in Rat Model - Ho-Joon Song; Myoung-Rae Cho (MEDrang Inc., 2018)
Background This study investigated the effects of acupuncture at Sobu (HT8) and Haenggan (LR2) on scopolamine-induced, cognitively impaired rats. Methods Scopolamine-treated Sprague-Dawley rats were divided into 6 groups; normal, control, HT8, LR2, HT8 + LR2 and sham group. Cognitive impairment was induced by scopolamine, in control, and then in HT8, LR2, HT8 + LR2 and sham groups. Acupuncture treatment was performed at HT8, LR2, HT8 + LR2, and a random acupoint, respectively, every other day for 2 weeks. After each treatment, behavior change was observed and the rats were sacrificed. The change in brain-derived neurotrophic factor, glutathione peroxidase, and superoxide dismutase activity was evaluated by polymerase chain reaction. Results Latency time to target in Morris Water-Maze test for the HT8 + LR2 group showed a significant decrease compared with control (p<0.05). Target crossing times and time zone ratios in Morris Water-Maze test for HT8 + LR2 group showed a significant increase compared with control (p<0.01). In the Y-Maze test the HT8 + LR2 group showed a significant increase compared with control (p<0.05). Brain-derived neurotrophic factor, glutathione peroxidase, and superoxide dismutase, in the HT8 + LR2 group, showed a significantly increased level compared with control (p<0.05). Neural activity of acetylcholine esterase in HT8 + LR2 group showed a significant decrease compared with the control group (p<0.01), choline acetyltransferase activity in the HT8 + LR2 group showed a significant increase compared with control (p<0.05). Conclusions Acupuncture at HT8 + LR2 restored scopolamine-induced cognitive impairment, suggesting acupuncture could be an alternative to improve cognitive function.